"Must I remember?": Hamlet, Memory, and Shakespearean Trauma - Lupić, Ivan (Array, 2008)
The chapter addresses the ethical dimension of studying Shakespeare (or, more precisely, of being a “ Shakespearean” ), starting with a discussion of a recent Croatian novel entitled William Shakespeare u Dar es Salaamu [William Shakespeare in Dar es Salaam]. The central character, a Bosnian refugee who finds shelter in Denmark in the 1990s, is described by some of the other characters we find in this narrative as a Shakespeare-phobe. To him, who has been tortured in concentration camps in Bosnia during the recent war, William Shakespeare is the worst name imaginable: it stands for pure evil and absolute horror. The well-known fact that one of the most prominent Shakespeare scholars in Bosnia was actively engaged in the creation and exercise of the aggressive war politics which caused so much gratuitous suffering in Bosnia during the 1990s (living and hurting still in the memories of many), provides occasion for some points to be made about the (metonymic) links between Shakespeare and his guardians, the Shakespeare scholars. Bringing together the themes of memory and trauma, the chapter queries the concept of “ the Shakespearean ethic” .